Performance analysis of a graph coloring algorithm for wavelength assignment in dynamic optical networks - Fonseca, P. (2022)
In the near future (5 to 10 years), dynamic optical networks will be crucial in global optical communications in order to respond to the fast growing of on-demand services. Routing and wavelength assignment (RWA) planning tools must be developed to effectively deal with the dynamic scenarios requirements. In this work, a simulation tool for RWA in dynamic optical networks was developed and wavelength assignment (WA) was implemented, through a recently proposed graph coloring algorithm, named Small-Buckets algorithm, that allows recolorings to occur. Several fiber based networks have been studied and it has been concluded that the Small-Buckets algorithm originates lower blocking probabilities than the ones obtained with the First fit algorithm. However, to reach this improved performance, the Small-Bucket algorithm requires a larger number of wavelengths and recolorings.